Update and review of the gerodontology prospective for 2020's: Linking the interactions of oral (hypo)-functions to health vs. systemic diseases - Yen Chun G. Liu; Shou-Jen Lan; Hirohiko Hirano; Li-min Lin; Kazuhiro Hori; Chia-shu Lin; Samuel Zwetchkenbaum; Shunsuke Minakuchi; Andy Yen-Tung Teng (Elsevier, 2021)
New lines of evidence suggest that the oral-systemic medical links and oral hypo-function are progressively transcending beyond the traditional clinical signs and symptoms of oral diseases. Research into the dysbiotic microbiome, host immune/inflammatory regulations and patho-physiologic changes and subsequent adaptations through the oral-systemic measures under ageism points to pathways leading to mastication deficiency, dysphagia, signature brain activities for (neuro)-cognition circuitries, dementia and certain cancers of the digestive system as well. Therefore, the coming era of oral health-linked systemic disorders will likely reshape the future of diagnostics in oral geriatrics, treatment modalities and professional therapies in clinical disciplines. In parallel to these highlights, a recent international symposium was jointly held by the International Association of Gerontology and Geriatrics (IAGG), Japanese Society of Gerodontology (JSG), the representative of USA and Taiwan Academy of Geriatric Dentistry (TAGD) on Oct 25th, 2019. Herein, specific notes are briefly addressed and updated for a summative prospective from this symposium and the recent literature.